Deficits in pain medication in older adults with chronic pain receiving home care: A cross-sectional study in Germany. - Juliana Schneider; Engi Algharably; Andrea Budnick; Arlett Wenzel; Dagmar Dräger; Reinhold Kreutz (PLoS ONE, 2020)
OBJECTIVE:To analyze the pattern and appropriateness of pain medications in older adults receiving home care. METHODS:We performed a prospective cross-sectional study in patients ≥65 years old having chronic pain and receiving home care in Berlin, Germany. Data on prescribed pain medications were collected using self-reported information, nursing documents, and medication plans during interviews at home. Pain intensity was determined with the numeric rating scale (NRS) and the Pain Assessment In Advanced dementia (PAINAD) scale. The Pain Medication Appropriateness Scale score (SPMAS) was applied to evaluate inappropriateness (i.e. a score ≤67) of pain medication. RESULTS:Overall 322 patients with a mean age of 82.1 ± 7.4 years (71.4% females) were evaluated. The average pain intensity scores during the last 24 hours were 5.3 ± 2.1 and 2.3 ± 2.3 on NRS and PAINAD scale (range 0-10, respectively). Sixty (18.6%) patients did not receive any pain medication. Among the treated patients, dipyrone was the most frequently prescribed analgesic (71.4%), while 50.8% and 19.1% received systemic treatment with opioids and non-steroidal anti-inflammatory drugs, respectively. The observed median SPMAS was 47.6 (range 0-100) with 58 (18.0%) of patients achieving appropriate values. Half of the patients were treated with scheduled, while 29.9% were only treated with on-demand medications. Cognitive status had no effect on appropriateness of pain treatment. CONCLUSIONS:We observed substantial deficits in dosing patterns and appropriateness of pain medication in older adults with pain receiving home care. This applied to both patients with and without severe cognitive impairment.